2003
DOI: 10.1017/s0967199403002181
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte age and nuclear donor cell type affect the technical efficiency of somatic cloning in rabbits

Abstract: The present study in rabbits compared, in the first experiment, the effect of two commonly used oocyte ages, 13 h and 17 h after ovulation induction treatment, on the technical efficiency of somatic nuclear transfer steps, using fresh cumulus cells as nuclear donors. Recently ovulated metaphase II oocytes (13 h) showed higher fusion (13 h: 83% vs 17 h: 67%, p < 0.05) and in vitro development rates than in vivo slightly aged metaphase II oocytes (morula, 13 h: 74% vs 17 h: 25%, p < 0.05; blastocyst, 13 h:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 53 publications
2
23
1
Order By: Relevance
“…Our data do not confirm results from previous studies, in which cumulus cells were found to be better (Cervera & Garcia-Ximenez 2003) Figure 2 Histone acH3K9/14 status of in vivo fertilized and cloned embryos. Normal: in vivo fertilized embryos.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data do not confirm results from previous studies, in which cumulus cells were found to be better (Cervera & Garcia-Ximenez 2003) Figure 2 Histone acH3K9/14 status of in vivo fertilized and cloned embryos. Normal: in vivo fertilized embryos.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have shown that while nuclear maturation (emission of the first polar body) was mildly affected, the potential to form blastocysts in vitro was significantly compromised in oocytes with a poor cumulus expansion (Feng et al, 2007;Han et al, 2006). Furthermore, rates of cell fusion and embryonic development of NT embryos decreased significantly when aged oocytes were used for recipient cytoplasts (Cervera and García-Ximénez, 2003;Iwamoto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many experimental designs in both research and clinical applications involve culture of matured oocytes prior to micromanipulation or insemination. For example, the cell cycle stage of the recipient cytoplasts must be finely controlled for the success of nuclear transfer for cloning (Zhou et al 2003, Wu et al 2007, and rates of cell fusion and embryonic development of nuclear transfer embryos decreased significantly when aged oocytes were used for recipient cytoplasts (Cervera & García-Ximénez 2003, Iwamoto et al 2005. Therefore, studies on the mechanisms and control of oocyte aging are important for the healthy reproduction of both humans and nonhuman mammals.…”
Section: Introductionmentioning
confidence: 99%